Structural elucidation of new urinary tamoxifen metabolites by liquid chromatography quadrupole time‐of‐flight mass spectrometry. (24th June 2014) - Lu, Jianghai; He, Chunji; He, Genye; Wang, Xiaobing; Xu, Youxuan; Wu, Yun; Dong, Ying; Ouyang, Gangfeng
<x xml:space="preserve">Abstract</x> In this study, tamoxifen metabolic profiles were investigated carefully. Tamoxifen was administered to two healthy male volunteers and one female patient suffering from breast cancer. Urinary extracts were analyzed by liquid chromatography quadruple time‐of‐flight mass spectrometry using full scan and targeted MS/MS techniques with accurate mass measurement. Chromatographic peaks for potential metabolites were selected by using the theoretical [M + H]+ as precursor ion in full‐scan experiment and m/z 72, 58 or 44 as characteristic product ions for N, N‐dimethyl, N‐desmethyl and N, N‐didesmethyl metabolites in targeted MS/MS experiment, respectively. Tamoxifen and 37 metabolites were detected in extraction study samples. Chemical structures of seven unreported metabolites were elucidated particularly on the basis of fragmentation patterns observed for these metabolites. Several metabolic pathways containing mono‐ and di‐hydroxylation, methoxylation, N‐desmethylation, N, N‐didesmethylation, oxidation and combinations were suggested. All the metabolites were detected in the urine samples up to 1 week. Copyright © 2014 John Wiley & Sons, Ltd.